Blockage of Galectin-Receptor Interactions Attenuates Mouse Hepatic Pathology Induced by Toxoplasma gondii Infection - He, Jian; Hou, Yongheng; Lu, Fangli (Frontiers in Immunology, 2022)
Toxoplasma gondii (T. gondii), one of the most important Apicomplexan protozoa, causes toxoplasmosis in human throughout the world. Galectin (Gal)-9 triggers a series of immune events via binding to its receptors, including T cell immunoglobulin and mucin-containing molecule 3 (Tim-3), CD137, CD44, and protein disulfide isomerase (PDI). To examine the regulatory role of galectin-receptor interactions in anti-toxoplasmic activities, C57BL/6 mice were infected with T. gondii RH strain and intraperitoneally injected alpha (α)-lactose to block the interactions of galectins and their receptors. Heatmaps showed upregulated values for Gal-9 and CD137 in the livers of T. gondii-infected mice and T. gondii-infected mice treated with α-lactose. Compared with T. gondii-infected mice, T. gondii-infected mice treated with α-lactose showed significantly increased survival rate, decreased tissue parasite burden, attenuated liver histopathology, increased mRNA expression levels of CD137, IFNγ, IL-4, and IL-10 in the liver, and increased Gal-9 mRNA expression level in the spleen. Correlation analysis showed that significant positive correlations existed between the mRNA expression levels of Gal-9 and CD137, Gal-9 and IFNγ, as well as between CD137 and IFNγ in the liver and spleen of T. gondii-infected mice; between CD137 and IFNγ in the liver of T. gondii-infected mice treated with α-lactose. In addition, blockage of galectin-receptor interactions showed enhanced M2 macrophage polarization in the liver of T. gondii-infected mice. Our data indicate that Gal-9-CD137 interaction may play an important role in controlling T. gondii proliferation and limiting liver inflammation in mice during acute T. gondii infection, through regulating T cell and macrophage immune responses.